Differences in Membrane Fluidity and Structure in Contact-Inhibited and Transformed Cells - Barnett, Ronald E. (1974)
Studies on contact-inhibited mouse embryo fibroblast 3T3 cells and 3T3 cells transformed by oncogenic RNA and DNA viruses and by a chemical carcinogen have demonstrated differences in plasma membrane architecture. Spin-label and freeze-fracture ultrastructural studies have shown that contact-inhibited cells have ordered membrane lipids and aggregated intramembranous particles, whereas transformed cells have fluid membrane lipids and randomly distributed intramembranous particles. These findings suggest a model for how changes in the cell membrane may account for some of the characteristic differences observed between contact-inhibited and transformed cells.